Rape myth acceptance among a population of college students - Price, Roxanne (My University, 1987)
This research examined the level of rape myth acceptance among college students living in residence halls. A survey was developed and employed to assess possible differences in rape myth acceptance based on the respondents' age, sex; academic class level, college of enrollment, residence hall living arrangement1 hometown community size1 acceptance of interpersonal violence, and personal exposure to the topic of rape. A total of 289 surveys were distributed to students living in residence hall housing. Fifty seven males and 110 females returned completed surveys. Rape myth acceptance scores were determined for each subject, with total possible scores ranging from 21 to 62, Analysis of responses revealed 111 respondents had low rape myth acceptance. Fifty six respondents indicated a moderate level of rape myth acceptance. None of the respondents showed a high acceptance of rape myths. Scores reflecting acceptance of interpersonal violence were also determined, with 10 respondents indicating a high acceptance of interpersonal violence. The chi-square test revealed significant differences (p<.05) in level of rape myth acceptance based on gender, with males showing a higher acceptance of rape myths than females. No significant differences (p<.05) were noted among respondents based on type of residence hall living arrangement, academic class level; or college of enrollment. The Spearman rank order correlation was employed to test the remaining null hypotheses; with significant relationships (p<.05) revealed in three areas. Both hometown community size and personal exposure to the topic of rape were inversely related to level of rape myth acceptance. Acceptance of interpersonal violence was positively related to level of rape myth acceptance (p<.001). No relationship was found between rape myth acceptance and respondents' age.
Keywords: College students -- Wisconsin -- La Crosse -- Attitudes; Public opinion -- Wisconsin -- La Crosse; Rape -- Public opinion